Opinión de los alumnos sobre una propuesta de retroalimentación correctiva de la expresión escrita en ELE - Francisco del Moral Manzanares (MediAzioni)
This paper describes a formative assessment experience in the classroom of Spanish as a foreign language (ELE) within the Italian university context with students at levels B1 and B2. During two different academic periods, some pedagogical principles proposed by Cassany (2006) were applied to the practice of written expression, with special emphasis on the feedback step. This feedback was provided through a marking code that identified errors without correcting them (indirect / implicit corrective feedback, cf. Bonilla López, 2021), highlighted the achievements, and suggested strategies to improve each student's performance. A questionnaire assessing the method used at the end of the course gauged overall student satisfaction and indicated potential improvements to be incorporated in the future.